Tecnologia educativa para prevenção de lesão por pressão: construção e validação - Marques, Mikaelle Fernandes (2023)
Home care is one of the tasks of the Primary Health Care (PHC) teams, it is important to involve the caregiver/family member and patient in the assistance provided at home, since the caregiver will be the direct support of the team of health professionals . Pressure injuries (PPL) are considered adverse events resulting from unsafe health care, which are responsible for dozens of debilitated, disabling patients and potentially causing death. Thus, in the search for the reduction of injuries, the nurse as a member of the PHC has a fundamental role in assisting with better care practices, in this context, educational technologies are inserted as instruments that facilitate the teaching- learning process. The aim of this study is to build an educational technology like a booklet on pressure injury prevention (PPI). This is a methodological research that was based on the development of an educational technology to help prevent pressure injuries, the scenario was the Primary Health Care in the municipality of Frecheirinha-Ce. For its implementation, Echer's methodological principles were followed, which initially carried out a bibliographical research on the subject in order to identify the scientific evidence available for the foundation of educational technology, an interview was carried out with caregivers to identify potentialities and challenges in the care provided for the prevention of PI. Then there was the development of the educational technology itself, materializing in the form of a booklet “Switch sides and avoid pressure: guidelines for caregivers”, finally, to assess the safety and efficiency of the material prepared, it went through a validation process so that it can later be used in practice, in this phase, eight expert judges participated in the subject, who analyzed the objectives, presentation, structure and relevance of the booklet. Thus, after validation, an instrument that enhances health care was obtained, because by providing information to caregivers, the intention is to support a prevention focused on home care to prevent PI and thus reduce its occurrence in patients with movement restrictions. This project was approved by the Research Ethics Committee (CEP) of the Universidade Estadual Vale do Acaraú (UVA), obtaining a favorable opinion with number: 5.321.658.